Advances in Post‐Combustion CO2 Capture by Physical Adsorption: From Materials Innovation to Separation Practice - Liu, Ru‐Shuai; Shi, Xiao‐Dong; Wang, Cheng‐Tong; Gao, Yu‐Zhou; Xu, Shuang; Hao, Guang‐Ping; Chen, Shaoyun; Lu, An‐Hui (ChemSusChem, 2021)
The atmospheric CO2 concentration continues a rapid increase to its current record high value of 416 ppm for the time being. It calls for advanced CO2 capture technologies. One of the attractive technologies is physical adsorption‐based separation, which shows easy regeneration and high cycle stability, and thus reduced energy penalties and cost. The extensive research on this topic is evidenced by the growing body of scientific and technical literature. The progress spans from the innovation of novel porous adsorbents to practical separation practices. Major CO2 capture materials include the most widely used industrially relevant porous carbons, zeolites, activated alumina, mesoporous silica, and the newly emerging metal‐organic frameworks (MOFs) and covalent‐organic framework (COFs). The key intrinsic properties such as pore structure, surface chemistry, preferable adsorption sites, and other structural features that would affect CO2 capture capacity, selectivity, and recyclability are first discussed. The industrial relevant variables such as particle size of adsorbents, the mechanical strength, adsorption heat management, and other technological advances are equally important, even more crucial when scaling up from bench and pilot‐scale to demonstration and commercial scale. Therefore, we aim to bring a full picture of the adsorption‐based CO2 separation technologies, from adsorbent design, intrinsic property evaluation to performance assessment not only under ideal equilibrium conditions but also in realistic pressure swing adsorption processes. Divide and conquer: This Review discusses the recent advances in adsorption‐based CO2 separation technology, from porous materials synthesis, adsorbents’ intrinsic property evaluation to performance assessments not only in view of the ideal equilibrium conditions but also in critically practical perspective.